ANALISA PENERAPAN LEAN WAREHOUSE DAN 5S+SAFETY DI GUDANG PT. NICHIRIN INDONESIA - Kusnadi, Kusnadi; Nugraha, Asep Erik; Wahyudin, Wahyudin (Universitas Suryakancana, 2018)
Abstract—The company has a problem in warehouse layout arrangement so it will cause some kind of waste in the warehouse such as long searching time when searching spare parts in warehouse, transportation time when bringing material to warehouse or from warehouse to outside warehouse and transportation time at time of arrangement of material to storage shelf. Besides the problem that is noticed is the handling of discontinue material and the completeness of safety for warehouse operators. The purpose of this study can know the whole activity and the kinds of waste that occurred, so that can be done to the improvement of activity in the storage. The method used in measurement using fishbone diagram, and use Tools 5S + Safety. Based on the calculation that utility use of warehouse space owned raw material PT. Nichirin Indonesia is close to 70%. Layout raw material for now 77% of raw material is already used for material storage. After the layout improvements, the utility of raw material usage is reduced to 37.11%. various wastes that occur among others, Waiting time on goods delivery activities from suppliers, Transportation time on activities to bring goods from outside to the receiving area, Waiting time because the material must wait arranged by the admin / operator who works, Transportation time at the time of setting goods to shelf and Searching time on activities to find material for production needs. To reduce the waste that occurred among others, Add material handling in the form of trolley goods and ladder to shorten the transportation time, Make changes to warehouse layout and Provide labeling / coding on each area of the material rackKeywords: Waste; Layout raw material; Fishbone diagram; Tools 5S + Safety